IMPLEMENTASI SISTEM INFORMASI KETENAGAAN PESANTREN (SIKAP) DALAM PENGELOLAAN TUNJANGAN GURU PENDIDIKAN DINIYAH DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAWA TIMUR. - Prifti Nensi Fira Zaida (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2025)
Management Information Systems reflect changes in the needs and demands for information management to support better performance and decision making, especially in government agencies such as the Ministry of Religion of East Java Province. Management Information Systems is designed to meet the needs of agencies and the public by providing easy and fast access, thereby producing accurate, up-to-date and relevant information for timely and effective decision making. With this, the Ministry of Religion for Early Education and Islamic Boarding Schools (PD Pontren) is integrating the Islamic Boarding School Personnel Information System (SIKAP) application. This application contains data on teaching staff in Islamic boarding school education and Islamic religious education and makes it easy for teaching staff to register to apply for teacher allowance assistance. The purpose of this research is to find out, (1) The process of managing pre-school education teacher allowances before the existence of the Islamic Boarding School Personnel Information System (SIKAP) at the Regional Office of the Ministry of Religion of East Java Province, (2) Implementation of the Islamic Boarding School Personnel Information System (SIKAP) in managing education teacher allowances diniyah at the Regional Office of the Ministry of Religion of East Java Province, (3) Evaluation of the Islamic Boarding School Personnel Information System (SIKAP) in managing the allowances for diniyah education teachers at the Regional Office of the Ministry of Religion of East Java Province. The research method used is descriptive qualitative. By using data collection techniques through observation, interviews and documentation. The data that has been obtained is processed using the process of data collection, data condensation, data presentation, and drawing conclusions. Data credibility is carried out by checking source triangulation procedures, methods and member checking. The results of this research show that, (1) The process of managing pre-school education teacher allowances prior to SIKAP was carried out manually, namely by prospective recipients of teacher allowances sending application files to the district/city Ministry of Religion, then verification and validation by the province, (2 ) Implementation of the Islamic Boarding School Personnel Information System (SIKAP) makes it easier for teachers to apply for allowances by uploading required files and does not need to come to the Ministry of Religion, and really helps the team in the process of verifying and validating teacher allowance management so that it is completed quickly and on time, (3) Evaluation of The Islamic Boarding School Personnel Information System (SIKAP) shows that this system has had a positive impact in managing the allowances for early education teachers at the Regional Office of the Ministry of Religion, East Java Province. The implementation of SIKAP has succeeded in cutting the time for managing allowances from months to a few days, as well as making work easier through the feature which can be done from anywhere.